A Combined Computational–Experimental Study of the Kinetics of Intramolecular Diels–AlderReactions in a Series of 1,3,8-Nonatrienes - Lording, W.; Payne, Alan; Cayzer, T.; Sherburn, M.; Paddon-Row, M. (CSIRO Publishing, 2014)
Activation enthalpies for a series of five 1,3,8-nonatriene intramolecular Diels–Alder (IMDA) reactions involving substrates 1–5 have been determined experimentally and Singleton’s natural abundance method has been employed to determine kinetic isotope effects in the IMDA reaction of fumarate 3. The activation enthalpies for the IMDA reactions of the systems possessing a –CH2OCH2– diene/dienophile tether are significantly smaller than their counterparts possessingthe –CH2OC(¼O)– tether. The experimental activation enthalpies have been used to benchmark computed values from four model chemistries, namely two density functional theory functionals, B3LYP and M06-2X, and two generally very accurate composite ab initio wave function methods, CBS-QB3 and G4(MP2). G4(MP2) outperformed the computationally more expensive CBS-QB3 method, but the vastly cheaper M06-2X/6-31G(d)//B3LYP/6-31G(d) method was sufficiently accurate to be the recommended method of choice for calculating activation parameters. Experimental 2H kinetic isotope effects for the IMDA reaction of fumarate 3 confirmed the computational predictions that this Diels–Alder reaction is concerted but asynchronous.